Perceived COVID-19 Severity, Risk of Infection, and Prevention Self-Efficacy in Saudi Arabia During Lockdown: A Population-Based National Study - Rajaa Al-Raddadi; Nezar Bahabri; Zeyad AlRaddadi (Springer, 2023)
Abstract Evidence shows that the risk perception of humans can significantly affect their response to a threat. This population-based, cross-sectional study explored the determinants of perceived disease seriousness, perceived disease infectiveness, and perceived prevention self-efficacy of coronavirus disease (COVID-19), during the lockdown period, using the health belief model for preventive behavior (HBMPB) among 4423 adults in Saudi Arabia from 13 provinces. Multivariate binary regression was used to analyze the independent factors of three risk perception variables and to measure their effect on adherence to preventive measures. Overall, COVID-19 seriousness was perceived to be higher than that of diabetes and lower than that of a heart attack, while its infectiousness was perceived to be high by 75.3% of the participants. Furthermore, 66.6% had a low perception of their prevention self-efficacy. The HBMPB showed independent effects of all three risk perception parameters on adherence to the preventive measures, including perceived seriousness (Odd's ratio [OR] = 1.26; 95% confidence interval [95% CI] = 1.01-1.56), infectiousness (OR = 1.90; 95% CI = 1.52-2.38), and prevention self-efficacy (OR = 1.51; 95% CI = 1.20-1.91). Authorities should maintain an optimal level of communication on the COVID-19 risk, communicate more about the virus' cycle and the disease to demystify the rationale of the preventive measures, and enhance confidence in their efficiency.